Earnings management, business strategy, and bankruptcy risk: evidence from Indonesia - Dian Agustia (Elsevier Ltd., 2020)
The purpose of this study is to examine the effect of accrual earnings management and business strategy to bankruptcy risk. Multiple Least Square (MLS) regression and robust regression of M-Estimator regression are performed on financial data of 1,068 non-financial firms listed on the Indonesia Stock Exchange (IDX). The result indicates that there is no relationship between earnings management and bankruptcy risk, while firms that implement either one of two generic business strategies of cost leadership or differentiation, significantly mitigate the risk of bankruptcy. The effect of earnings management to bankruptcy risk is essential for external stakeholders, such as investors and creditors, to assess bankruptcy risk, financial capability, and credit worthiness of a firm, while business strategy effect on bankruptcy risk benefits internal stakeholders, such as managers, in formulating strategies to deal with going concern issues.